ASPEK SPASIAL MITIGASI DAN PERKIRAAN RESIKO BENCANA GEOLOGI PADA EKS LAHAN TAMBANG MENGGUNAKAN CITRA LANDSAT-8 - Tahir, Tahir; Yusuf, Daud; Hendra, Hendra (Universitas Negeri Makassar, 2023)
Mitigation of geological disaster risks in former mining areas is generally defined as an action to reduce the risk of losses due to geological processes (landslides, soil erosion, flooding, and flash floods). In addressing the mitigation of geological disaster risks, planning strategies are required, especially regarding the need for geological disaster mitigation management. The strategic steps of geological disaster mitigation management in former mining areas aim to prevent geological disasters from causing greater impacts. The occurrence of geological disasters is usually given attention only after the disaster has happened. This is a consequence of a lack of understanding and awareness that managing geological disasters, especially those in former mining areas (landslides, soil erosion, flooding, and flash floods), involves a series of geological disaster mitigation management applied at every phase of disaster management activities, including during the formulation of environmental management policies in former mining areas. The character and typology of estimated geological disaster risks in Southeast Sulawesi, especially in former mining areas, include geological disasters causing landslides, soil erosion, flooding, and flash floods. The concept of an action plan for mitigating landslide, soil erosion, flooding, and flash flood disasters, is integrated into the spatial aspect of geological disaster mitigation management. There are four spatial aspects in planning the mitigation of geological disaster risks in former mining areas, namely: (1) hazard identification; (2) vulnerability identification; (3) risk assessment; and (4) land use planning. Geological disaster mitigation management must be able to integrate these four aspects in accordance with prevention strategies and the reduction of geological disaster risks, including the formulation of policies for mitigating geological disasters. Geological disaster mitigation planning should consider processes that are predicted to result in geological disaster risks (landslides, soil erosion, flooding, and flash floods) in former mining areas. Thus, geological disaster mitigation in former mining areas needs to be seriously addressed to avoid negative impacts on the community, especially those living around locations predicted to experience geological disasters